2021
DOI: 10.3389/fpls.2020.622209
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycrorrhizal Fungi Inoculation and Applied Water Amounts Modulate the Response of Young Grapevines to Mild Water Stress in a Hyper-Arid Season

Abstract: Several factors may affect the success of a replanting vineyard. Given the current environmental conditions, an optimized irrigation schedule would still be one of the most desirable tools to improve crop productivity and fruit quality. On the other hand, the symbiosis of grapevines with arbuscular mycorrhizal fungi (AMF) is a key component of the vineyard production systems improving the vine growth, nutrient uptake, and berry quality. The aim of this study was to characterize the response of Merlot grapevine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Previous research suggested that these effects might be related to the altered regulation of nutrient transport, cell wall-related, phenylpropanoid, and stilbene biosynthesis genes driven by AMF colonization (Bruisson et al, 2016 ; Balestrini et al, 2017 ). Additionally, it was recently reported that AMF may enhance the content of flavonoids in berries (Torres et al, 2019 , 2021a ), leading to improved berry composition and antioxidant properties in spite of the lack of effect on petiole nutrient contents (Torres et al, 2021a ). However, vineyard management practices may affect the soil structure and the composition of the rhizosphere-living microbiota (Coller et al, 2019 ; Vink et al, 2021 ), as well as the microbiota associated with grapevine roots, which is mainly composed by Rhizophagus and Glomus genus (Schreiner, 2020 ), likely affecting the effectiveness of the symbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research suggested that these effects might be related to the altered regulation of nutrient transport, cell wall-related, phenylpropanoid, and stilbene biosynthesis genes driven by AMF colonization (Bruisson et al, 2016 ; Balestrini et al, 2017 ). Additionally, it was recently reported that AMF may enhance the content of flavonoids in berries (Torres et al, 2019 , 2021a ), leading to improved berry composition and antioxidant properties in spite of the lack of effect on petiole nutrient contents (Torres et al, 2021a ). However, vineyard management practices may affect the soil structure and the composition of the rhizosphere-living microbiota (Coller et al, 2019 ; Vink et al, 2021 ), as well as the microbiota associated with grapevine roots, which is mainly composed by Rhizophagus and Glomus genus (Schreiner, 2020 ), likely affecting the effectiveness of the symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Root samples were cleaned, cleared, and stained according to methods described in Koske and Gemma (1989). Fifty root segments per replicate (∼1 cm each) were examined under the microscope to determine intraradical AMF colonization as previously described in Torres et al (2016Torres et al ( , 2021a. Briefly, the extension of mycorrhizal colonization was determined by estimating its product in width and length according to a scale range between 0 and 10, where 0 is the complete absence of fungal structures.…”
Section: Amf Colonizationmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive effect on plant biomass, osmolytes, and antioxidant enzyme activity under drought was noted in Zenia insignis [11], while alleviating the effect of AMF on Knautia arvensis drought stress was supported by lower proline accumulation [12]. Higher water-use efficiency in mycorrhizal wheat was also noted [13], and a few pieces of research have reported that AMF symbiosis increased grapevine tolerance to water stress and increased water-use efficiency [2,18].…”
Section: Introductionmentioning
confidence: 97%